Revisiting the diversity of Ludioctenus Fairmaire (Elateridae: Agrypninae), with description of a new species from Afghanistan, and discussion on the systematic position of Tetrigusina - Kundrata, Robin; Sormova, Eliska; Prosvirov, Alexander S. (Zootaxa, 2018)
The genus Ludioctenus Fairmaire, 1893 hitherto included only L. cyprius (Baudi di Selve, 1871) from the eastern Mediterranean and L. pakistanicus Schimmel & Tarnawski, 2012 from Pakistan. Here, we describe L. afghanicus sp. nov. from the Nuristan Province in eastern Afghanistan. The distribution and morphological diversity of Ludioctenus is discussed, main diagnostic characters for all species are figured, and an identification key to the species of this genus is provided. Female pregenital segments and genitalia are figured for the first time for Ludioctenus, and the systematic position of this genus and its relatives is discussed.